Growth Hormone Deficiency in Patients with Sickle Cell Disease and Growth Failure - Nunlee-Bland, G.; Rana, S.R.; Houston-Yu, P.E.; Odonkor, W. (Journal of Pediatric Endocrinology and Metabolism, 2004)
Growth disorders are common in children with sickle cell disease (SCD). The etiology for growth disturbances in this population appears to be multifactorial. Recent evidence suggests abnormalities in the growth hormone (GH)/insulin-like growth factor-I (IGF-I) and IGF binding protein-3 (IGFBP-3) axis may play a role. To measure GH levels through provocative stimulation in a group of patients with SCD with growth failure, and to evaluate response to treatment. Growth records were reviewed of 79 children with sickle cell hemoglobinopathies to identify children with growth failure. GH levels were measured in patients with SCD with and without growth failure using arginine and L-Dopa as provocative stimulation tests. Treatment with GH was offered to GH-deficient children with SCD and these patients were followed longitudinally over 5 years. Of the 79 patients, 13 (16.5%, all SS) had heights less than -2 SD below the mean or a growth velocity < -2 SD below the mean for age. Seven of the 13 children with growth failure participated in this study. Five patients received GH for 3 or more years and demonstrated significant improvement in their height SDS. One of the two who declined treatment was lost to follow-up and the other had significant worsening of height SDS score. GH deficiency may be associated with growth failure in some patients with SCD. These patients may benefit from treatment with GH.